Clinical outcome of intra-articular hyaluronic acid injection for knee joint osteoarthritis: a prospective interventional study from a tertiary care hospital - Sudheer, Urampath; Jayaprakash, Chundarathil (International Journal of Research in Orthopaedics, 2017)
Background: The prevalence of knee osteoarthritis (OA) is estimated to be 14% and 6% in rural and urban areas of India, respectively. In severe cases, the American Academy of Orthopedics Surgeons recommends non-steroidal anti-inflammatory drugs (NSAIDs). A prospective interventional study was conducted to evaluate the effectiveness of intra-articlular hyaluronic acid injection (IAHA) in knee OA patients. Methods: Medical records of 29 patients with knee OA, who were treated with IAHA injection, were analyzed using a 24 item WOMAC scale for the pain, stiffness, and physical function scores. Furthermore, the patients’ quality of life was evaluated based on the SF-12 scale and a global status assessment of knee OA was performed using the Likert scale and visual analogue scale (VAS). The data were analysed statistically. Results: The overall WOMAC pain, stiffness, and physical function scores decreased following the IAHA administration in patients with knee OA. The mean pain scores decreased from 10.82 to 3.62 and stiffness scores dropped from 4.34 to 2.03. The mean physical function scores decreased from 36.75 to 17.1 (p<0.0001). The Likert scale and VAS demonstrated statistically significant (P < 0.0001) improvement in the patient’s health status. Overall, nearly 80% of the patients expressed little-to-none physical or emotional problems four weeks after IAHA treatment. Conclusions: A single IAHA injection provided statistically significant improvement in pain, disability, and quality of life in knee OA patients.